Großstadtpolitik in England — Das Beispiel Manchester - Jessen, Johann; Walther, Uwe-Jens (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
When elected in 1997, the British Labour Government made urban policy one of its key policy concerns. Criticism of the shortcomings of previous, predominantly market oriented urban policy, was combined with new approaches to state action. Numerous programmes were developed, new institutions created and urban policy initiatives were launched which are still reflected in both national and municipal urban policy in England. The urban policy of the Blair government has received an overall favourable assessment in recent evaluative reports. Such studies conclude that in the towns and cities social cohesion has grown over the last ten years, they have become more competitive and the quality of life, which in England is commonly defined in relation to the quality of public space, has risen. This article outlines the main features of this urban policy over the last ten years. It takes the example of Manchester’s urban policy, widely regarded as a particularly successful and notable case, to demonstrate policy outcomes.